Association of Chlamydia trachomatis with persistence of high-risk types of human papillomavirus in a cohort of female adolescents - Samoff, Erika; Koumans, Emilia H; Markowitz, Lauri E; Sternberg, Maya; Sawyer, Mary K; Swan, David; Papp, John R; Black, Carolyn M; Unger, Elizabeth R (American journal of epidemiology, 2005)
Human papillomavirus (HPV) infection is a necessary but not sufficient cause of cervical cancer. While chlamydia infection has been associated with cervical cancer, the meaning of this association remains unclear. The authors' objective was to investigate this association by evaluating whether concurrent genital tract infections are associated with HPV persistence, a precursor to cervical cancer. Interview data and biologic samples for HPV, Chlamydia trachomatis, Neisseria gonorrhoeae, Trichomonas vaginalis, and bacterial vaginosis testing were collected from female adolescents in an Atlanta, Georgia, longitudinal cohort study at 6-month visits (1999-2003). Associations with persistence (detection of the same HPV type at two sequential visits (visit pair)) were assessed among subjects with 2-5 visits and > or =6 months of follow-up. Associations were evaluated by logistic regression using methods for correlated data. Type-specific persistence of high-risk HPV types was detected in 77 of 181 (43%) analyzed visit pairs. Concurrent infection with C. trachomatis was independently associated with persistence of high-risk HPV types (adjusted odds ratio = 2.1, 95% confidence interval: 1.0, 4.1). Infection with more than one HPV type at the initial visit was also associated with high-risk persistence (adjusted odds ratio = 2.8, 95% confidence interval: 1.6, 4.9). The association between chlamydia infection and cervical cancer may be due to an effect of chlamydia infection on persistence of high-risk HPV.